Mechanical Activation of Graphite for Na-Ion Battery Anodes: Unexpected Reversible Reaction on Solid Electrolyte Interphase via X-Ray Analysis - Lee, Su Chan; Kim, Young Hwan; Park, Jae-Ho; Susanto, Dieky; Kim, Ji-Young; Han, Jonghyun; Jun, Seong Chan; Chung, Kyung Yoon (Wiley-VCH Verlag, 2024)
Although sodium-ion batteries (SIBs) offer promising low-cost alternatives to lithium-ion batteries (LIBs), several challenges need to be overcome for their widespread adoption. A primary concern is the optimization of carbon anodes. Graphite, vital to the commercial viability of LIBs, has a limited capacity for sodium ions. Numerous alternatives to graphite are explored, particularly focusing on disordered carbons, including hard carbon. However, compared with graphite, most of these materials underperform in LIBs. Furthermore, the reaction mechanism between carbon and sodium ions remains ambiguous owing to the structural diversity of disordered carbon. A straightforward mechanical approach is introduced to enhance the sodium ion storage capacity of graphite, supported by comprehensive analytical techniques. Mechanically activated graphite delivers a notable reversible capacity of 290.5 mAh<middle dot>g-1 at a current density of 10 mA<middle dot>g-1. Moreover, it maintains a capacity of 157.7 mAh<middle dot>g-1 even at a current density of 1 A<middle dot>g-1, benefiting from the defect-rich structure achieved by mechanical activation. Soft X-ray analysis revealed that this defect-rich carbon employs a sodium-ion storage mechanism distinct from that of hard carbon. This leads to an unexpected reversible reaction on the solid electrolyte surface. These insights pave the way for innovative design approaches for carbon electrodes in SIB anodes. Graphite, vital to the commercial viability of lithium-ion batteries (LIBs), has a limited capacity for sodium ions. Numerous alternatives to graphite are explored, particularly focusing on disordered carbons, including hard carbon. However, compared with graphite, most of these materials underperform in LIBs. A straightforward mechanical approach is introduced to enhance the sodium ion storage capacity of graphite, supported by comprehensive analytical techniques. image